ADMINISTRATIVE PROCEDURE ACCORDING TO FOUR SANGAHAVATTHU OF THE PHUTTHAMONTHON POLICE STATION, PHUTTHAMONTHON DISTRICT, NAKHONPATHOM PROVINCE - Phamorncham, Chakrkrich; Phathong, Ketsada; Chimmakun, Arada (Journal of MCU Social Science Review, 2022)
The research article was to study opinions and compare opinions and administrative practices according to four Sangahavatthu of the Bhutthamonthon Police Station, Bhutthamonthon District, Nakhon Pathom Province. The methodology was the mixed methods. The quantitative research, data were collected from 368 samples, by distributing questionnaires. the statistics used were frequency, percentage, mean, and standard deviation. The qualitative research, data were collected by interviewing 5 key informants and analyzed by descriptive content interpretation. The results of the study were found that: 1. People's opinions on administrative procedure by overall were at high level, sorting from the highest to the lowest means, namely administrative work, Investigation work, traffic work, and prevention and suppression work, respectively. 2. Comparative results were found that the people with different education, occupation, and income had different opinions at the statistically significant level at 0.05. The people with different gender and age did not have different opinions, 3. The suggestion was that the administrative procedure according to four principles of Sangahavatthu were as follows: 1) administrative work; police officers should give advice, supervise the discipline, regulations, and regulations. using respectful words and behave beneficially. 2) prevention and suppression; the police must pay attention and act to prevent both drugs and crime. 3) investigative work; the police should not let the case remain. 4) traffic work; police should provide knowledge according to educational institutions in the area of responsibility, provide knowledge about traffic rules, regulations, traffic signs, and various traffic signs to students and drivers.